Regulation of actin filament assembly and disassembly in growth cone motility and axon guidance - Schneider, Felix; Metz, Isabell; Rust, Marco B. (Brain research bulletin, 2023)
Directed outgrowth of axons is fundamental for the establishment of neuronal networks. Axon outgrowth is guided by growth cones, highly motile structures enriched in filamentous actin (F-actin) located at the axons’ distal tips. Growth cones exploit F-actin-based protrusions to scan the environment for guidance cues, and they contain the sensory apparatus to translate guidance cue information into intracellular signaling cascades. These cascades act upstream of actin-binding proteins (ABP) and thereby control assembly and disassembly of F-actin. Spatiotemporally controlled F-actin dis-/assembly in growth cones steers the axon towards attractants and away from repellents, and it thereby navigates the axon through the developing nervous system. Hence, ABP that control F-actin dynamics emerged as critical regulators of neuronal network formation. In the present review article, we will summarize and discuss current knowledge of the mechanisms that control remodeling of the actin cytoskeleton in growth cones, focusing on recent progress in the field. Further, we will introduce tools and techniques that allow to study actin regulatory mechanism in growth cones.
Online veröffentlicht am 3. November 2022, Version vom 5. November 2022
Gesehen am 17.01.2023